Redressing the silence: Photography, memory and the Great Famine - Carpenter, Paul Anthony Matthew (Curtin University, 2015)
Much has been said regarding the presumption of silence surrounding the Great Irish Famine (1845-1852). During and since the event’s sesquicentennial commemoration in the mid-1990s, this silence has been examined by scholars from diverse fields. Following these developments, this thesis examines how Photography’s enigmatic mix of referential and allegoric possibilities might, by uncovering the Famine’s traces, provide insights into the event, its memory and the class of cottiers and landless labourers who were obliterated by it.